186 Dorsal Root Ganglion Stimulation as Rescue Therapy for Intractable Pain Following Failed Spinal Cord Stimulation. (1st April 2022) - Mandelberg, Nataniel; Chapman, Kenneth; Spiegel, Matthew; van Helmond, Noud; Patel, Kiran; Yang, Ajax; Deer, Timothy R.; Mogilner, Alon Y.
Abstract : INTRODUCTION: Despite the demonstrated benefits of spinal cord stimulation (SCS) in patient suffering from chronic pain, loss of efficacy continues to be the primary reason for explant. In order to restore relief in these failed patients, delivery of alternative electrical current can be considered to 'salvage' the therapy. Dorsal root ganglion stimulation (DRG-S) is a neuromodulatory technique which acts on a different anatomic target, thereby yielding distinct mechanisms of action and should be considered for such salvage therapy. METHODS: This was multicenter retrospective chart review over years 2016-2020 of habituated SCS patients who were later salvaged with DRG-S. Primary endpoints were health related quality of life metrics. Data was gathered preop salvage DRG-S and compared to patients' last follow-up. RESULTS: Fifty-five failed SCS patients were salvaged with DRG-S. The median age was 57 and the most common diagnoses were complex regional pain syndrome and failed back surgery syndrome. Failed waveforms included tonic (n = 27), high frequency (n = 9) and burst (n = 19). The majority of DRG-S leads were placed at bilateral T12 and S1. The mean follow up duration of salvage DRG-S was 27 months. All indices were significantly improved with salvage DRG-S. Numeric rating scale scores decreased from mean 8.7 to 3.8, with 80% of patients achieving at least one minimum clinically important difference ( = 30% improvement). Mean Oswestry disability index scores improved from 65 to 31, signifying an improvement from mostly crippled to moderate disability. EQ5D-5L improved from 0.402 to 0.732. Oral morphine equivalents declined from mean 62 to 38. CONCLUSION: These data strongly support DRG-S efficacy in the stable treatment of pain in patients who have previously failed to receive persistent benefit from dorsal column SCS. DRG-S therapy reduces pain and disability while improving quality of life.